Oncofertility outcomes after fertility-sparing surgery in infertile BOT patients: results of a large retrospective study on controlled ovarian stimulation - Liang, Liang; Zhen, Xiu-Mei; Li, Yuan; Ma, Cai-Hong; Yang, Shuo; Yan, Jie; Song, Xue-Ling; Li, Rong (Frontiers in Oncology, 2025)
PurposeThe optimal management of borderline ovarian tumors (BOTs), particularly the safety and efficacy of in vitro fertilization (IVF) following fertility-sparing surgery (FSS), remains controversial. This study aimed to evaluate the impact of controlled ovarian stimulation (COS) on oncofertility outcomes in infertile women with BOT after FSS.MethodsThis retrospective observational study was conducted at the Reproductive Medical Center, Peking University Third Hospital (Beijing, China) and included 73 infertile BOT patients who underwent IVF between January 2008 and June 2022.ResultsMedian follow-up was 61.0 months (range: 7.0–156.0 months). The BOT recurrence rate was 20.5% (15/73), and the cumulative live birth rate per patient was 57.5% (42/73). There were no significant differences in the number of COS cycles (P=0.513) or total dose of gonadotropin (Gn) (P =0.183) between the recurrence and non-recurrence groups. Multivariate analysis identified three independent predictors of oncologic outcomes: interval from surgery to first IVF (HR: 0.07; 95% CI: 0.01–0.44; P =0.004), duration of Gn administration (HR: 9.70; 95% CI: 1.37–68.70; P =0.023), and live birth (HR: 7.02; 95% CI: 1.35–36.41; P=0.020).ConclusionIn infertile BOT patients undergoing FSS, IVF significantly improves pregnancy outcomes. COS can be safely conducted post-FSS without increasing recurrence risk, provided initiation is delayed ≥3 months postoperatively and Gn administration is limited to ≤13 days.